When Is Simultaneous Recording Necessary? A Guide for Researchers Considering Combined EEG-fMRI - Scrivener, Catriona L. (Frontiers in Neuroscience, 2021)
Electroencephalography (EEG) and functional magnetic resonance imaging (fMRI) provide non-invasive measures of brain activity at different spatial and temporal scales, offering different views on brain function for both clinical and experimental applications. Simultaneous recording of these measures attempts to maximise the respective strengths of each method, while compensating for their weaknesses. However, combined recording is not necessary to address all research questions of interest, and experiments may have greater statistical power to detect effects by maximising the signal to noise ratio in separate recording sessions. While several existing papers discuss the reasons for or against combined recording, this article aims to synthesise these arguments into a flow-chart of questions that researchers can consider when deciding whether to record EEG and fMRI separately or simultaneously. Given the potential advantages of simultaneous EEG-fMRI, the aim is to provide an initial overview of the most important concepts and to direct readers to relevant literature that will aid them in this decision.